Analysis of the Effectiveness of the Huma Betang Public Service Mall (MPP) in Realizing Transparency in the Public Services of the Samsat Office of Palangka Raya City - Septiana Olipia; Tara Eli Sabtiani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Public Service Mall (MPP) is a government effort to improve the quality of public services through the integration of various services in one place, thus expected to provide easier, faster, and more efficient services for the public. The presence of the MPP is also part of bureaucratic reform in realizing transparent and accountable services. However, in its implementation there are still challenges, such as limited public understanding of the service flow and the involvement of third-party intermediaries. The presence of the Samsat Corner at the Public Service Mall (MPP) Huma Betang, Palangka Raya City is expected to be able to overcome these problems through faster and more open services. This study aims to analyze the effectiveness and transparency of the Samsat Corner service at the MPP Huma Betang. The method used is a qualitative approach through observation and interviews with community service users and service officers. The results of the study indicate that the service has been running quite effectively, as evidenced by a completion time of around 5-10 minutes, then simple procedures, and friendly officers in service. However, transparency has not been optimally implemented because some people do not understand the flow and cost information clearly. In addition, the involvement of brokers is still found outside the service area.